HUBUNGAN KONTROL DIRI DENGAN PERILAKU KONSUMTIF PADA REMAJA DI KOMUNITAS PENGGEMAR K-POP ARMY GORONTALO - Lenny Syamsuddin; Suryan Y. Akuba (Elsia: Jurnal Psikologi Manusia, 2022)
Self-control is an individual's ability to modify behavior, as well as an individual's ability to choose an action. Consumptive behavior is the actions of individuals who are directly involved in obtaining goods and services. This research was conducted in the Gorontalo Army community. The Objective of this research was to determine the relationship between self-control and consumptive behavior in adolescents in the Gorontalo K-Pop Army fan community. Product moment correlational quantitative research method. The sample amounted to 67 respondents. The technique used for sampling is total sampling technique. Data was collected using 2 scales, namely the self-control scale with consumptive behavior. Testing the hypothesis using bivariate analysis showed that there was a significant and positive relationship between self-control and consumptive behavior in adolescents in the Army Gorontalo community. r value shows a value of 0.664 which means, there is a negative relationship between the two variables. This means that the stronger the self-control, the lower the consumptive behavior and vice versa, the weaker the self-control, the stronger the consumptive behavior.